The Crucial Role of Evidence and Witness Testimony in International Criminal Court War Crimes Prosecutions - Maruma, Kholofelo (International Journal of Humanities and Education Development (IJHED), 2025)
This paper delves into the pivotal role of evidence and witness testimony in the prosecution of war crimes by the International Criminal Court (ICC). The International Criminal Court, tasked with addressing the most severe crimes of international concern, relies heavily on solid evidence and credible witness testimonies to secure convictions. This study scrutinizes the processes and challenges involved in collecting and presenting evidence, as well as the importance of witness protection and support mechanisms. Through an in-depth analysis of past International Criminal Court cases, the paper underscores the impact of evidence and witness testimony on the outcomes of war crimes prosecutions. The findings highlight the necessity for stringent evidentiary standards and effective witness management to ensure justice and accountability in international criminal law. This research contributes to a broader understanding of the complexities and significance of evidence and witness testimony in the pursuit of justice for war crimes.